Pipeline for development of acylated peptide based CGRP receptor antagonist with extended half-life for migraine treatment - Jens Bjelke Kristensen; Lisbeth Elster; Morten Lundh; Borja Ballarín-González; Flora Alexopoulou; Martin Kræmer; Ditte Marie Jensen; Ulrike Leurs; Jens Christian Nielsen; Henrik H. Hansen; Kristian A. Haanes; Matilda Degn (Scientific Reports)
Abstract Migraine is a debilitating headache disorder. The disease has neurovascular origin and migraine attacks can be elicited by vasodilative neuropeptides such as alpha calcitonin gene-related peptide (αCGRP). Antagonizing CGRP actions in migraine patients has proven clinically efficient. Here, we present a pipeline for development of a peptide-based hCGRP receptor antagonist with increased half-life capable of antagonising the vasodilatory effect of hαCGRP. A series of hαCGRP8-37 analogues carrying a C18-or C20-diacid lipidation was screened for their antagonism against the hCGRP receptor. hαCGRP8-37 analogues with a C20-diacid were 2-6 fold more potent than analogues conjugated with a C18-diacid. Half-life of hαCGRP8-37 analogues carrying a C20-diacid was estimated in mice in a pilot study (n = 1–2). Half-lives ranged from 7.3 to 13.7 h. An hαCGRP8-37 analogue conjugated with a C20 diacid at position 25 was subjected to an amino acid substitution scan to identify mutations that could further enhance hCGRP receptor antagonism. Substituting alanine with serine at position 36 resulted in a ~ 4 fold gain of potency. Vasodilative actions of hαCGRP were successfully antagonized by hαCGRP8-37 analogues carrying a C20 diacid at position 25. Our findings demonstrate that lipidation can improve hαCGRP8-37 pharmacokinetics while maintaining hαCGRP antagonism, thus demonstrating potential for a peptide-based migraine treatment strategy.